The US-China Trade War and Global Reallocations - Fajgelbaum, Pablo (World Bank, Washington, DC, 2022)
This paper studies global trade responses to the US-China trade war. It estimates the tariff impacts on product-level exports to the US, China, and rest of world. On average, countries decreased exports to China and increased exports to the US and rest of world. Most countries export products that complement the US and substitute China, and a subset operate along downward-sloping supplies. Heterogeneity in responses, rather than specialization, drives export variation across countries. Surprisingly, global trade increased in the products targeted by tariffs. Thus, despite ending the trend towards tariff reductions, the trade war did not halt global trade growth.